Performance differences between winning and losing basketball teams during close, balanced and unbalanced quarters - Csataljay, G.; James, N.; Hughes, M.; Dancs, H. (Journal of Human Sport & Exercise, 2012)
Previous studies in basketball performance have tended to assess differences between winners and losers of games. This methodology does not consider the fluctuating nature of scoring within games. Consequently winning and losing performance for each quarter of 26 games of the Hungarian basketball league in 2007/08 were compared with the difference in points scored used as an independent variable with three levels (identified through cluster analysis as close (1 to 5 points), balanced (6 to 11 points) and unbalanced periods (12 to 22 points)). Wilcoxon signed ranks tests identified significant differences between winning and losing quarter performance for 20 performance indicators when all quarters were analysed (n = 100) in comparison to just 5 for close quarters only (n = 42). The five performance indicators (number of successful free throws, number of defensive rebounds, total amount of rebounds and rebounding percentage in offence and defence) suggest that mainly the success in rebounding might be the critical factor that determines winning and losing in these close situations. Kruskal Wallis H tests and Mann Whitney U post-hoc tests revealed differences between winning performances from close, balanced and unbalanced quarters for the 3 point performance (number of successful 3 point shots, number of 3 point attempts and 3 point shooting performance), the number of assist passes and turnovers; these findings could be explained by the significantly different features of defensive resistance during different types of periods.